Weighted Integral Representations in Tube Domain Over Real Unit Ball - Karapetyan, Arman H. (Sarajevo Journal of Mathematics, 2024)
Weighted spaces of functions holomorphic in tube domain over the real unit ball of $R^n$ are considered. For these classes reproducing kernels are constructed in an explicit form. Estimates for these kernels are obtained.